Analisis Pengaruh Sabut Kelapa Terhadap Kekuatan Impact Dan Kekerasan Material Komposit Bermatriks Epoxy - Baihaqi, Ahmad Adi; Waluyo, Marhadi Budi; Murdianto, Deny (Faculty of Engineering, Universitas Borneo Tarakan, 2024)
Coconut fiber is one of the versatile natural materials with various applications in various industries. Coconut fiber is used in the manufacture of ropes, fabrics, and other textile products. This fiber is often used in the production of sacks, mats, and wickerwork. Coconut fiber can be used as a mixture in the manufacture of concrete and other building materials. Coconut fiber can also be used as a composite material. Composites consist of two elements, namely matrix and filler. This study aims to determine the effect of coconut fiber variations on impact strength and hardness. The composition of the filler is around 10, 15, 20 (%) of coconut fiber with matrix resin. The addition of filler is accompanied by a reduction in the matrix used from 100% epoxy. Specimens with NaOH treatment were made with 9 specimens and without treatment were made as many as 3 specimens. Composites were made by hand lay-up process. The composites that have been made were then subjected to mechanical tests, namely hardness and impact. The highest hardness test data results with NaOH treatment at variation (15%/85%) were 75 shore D. The lowest hardness at variation (10%/90%) was 63 Shore D. While without treatment the research results showed the highest at variation (10%/90%) was 74 Shore D. And the lowest hardness at variation (20%/80%) was 63 Shore D. The highest impact strength of NaOH treatment was at variation 20% absorbed energy of 3.28 Joules and impact toughness of 0.020 J/mm2. The highest untreated composite was at variation 20% absorbed energy 0f 3.39 Joules and impact toughness of 0.021 J/mm2.